2019
DOI: 10.1186/s40645-019-0282-1
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-thaw durability of repair mortars and porous limestone: compatibility issues

Abstract: Freeze-thaw cycles can cause considerable damage to porous materials and thus have an adverse effect on the durability of mortars and porous stone. To assess the behavior and frost resistance of two types of porous limestone, three commercially available repair mortars and four mixtures of laboratory-prepared repair mortars were subjected to freeze-thaw cycles according to EN 12371. During the test, samples of stone and mortar were bonded together and the weight loss was continuously monitored. The adhesion bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
(71 reference statements)
1
16
0
Order By: Relevance
“…In this line, the calcarenites cemented by smaller calcite grains and with higher pore size (BC-Y1 and BC-Y2) exhibit greater strength reductions due to water saturation than the varieties cemented by greater calcite grains and with lower pore diameters (BC-BL, BC-BG and BC-DM). These results are in agreement with those found by Török [49], Papay and Török [50] and Török and Szemerey-Kiss [51], [52], who observed that the limestones cemented by fine grained micrite calcite are more water sensitive in terms of strength and durability than those cemented by micro-sparitic calcite. In addition, they also found the existence of a close relationship between the pore structures and the mechanical properties of Hungarian limestones.…”
Section: Variation Of Mechanical Properties Due To Water Saturationsupporting
confidence: 92%
“…In this line, the calcarenites cemented by smaller calcite grains and with higher pore size (BC-Y1 and BC-Y2) exhibit greater strength reductions due to water saturation than the varieties cemented by greater calcite grains and with lower pore diameters (BC-BL, BC-BG and BC-DM). These results are in agreement with those found by Török [49], Papay and Török [50] and Török and Szemerey-Kiss [51], [52], who observed that the limestones cemented by fine grained micrite calcite are more water sensitive in terms of strength and durability than those cemented by micro-sparitic calcite. In addition, they also found the existence of a close relationship between the pore structures and the mechanical properties of Hungarian limestones.…”
Section: Variation Of Mechanical Properties Due To Water Saturationsupporting
confidence: 92%
“…The pore structure also influences the water absorption and thus the frost resistance of the stone [20]. The differences in the porosity of stone and mortar, the compatibility [5] might lead to differential weathering and loss of stone material. The different moisture content of different lithotypes suggests that the porosity and poresize distribution of various limestone types are different, and thus their resistance against freeze-thaw related weathering is also different.…”
Section: Non-destructive Surface Strength -Schmidt Hammermentioning
confidence: 99%
“…17), while in medieval lime-based mortars quartz grains dominate. These differences can also contribute to the differences in durability [1,5].…”
Section: Microscopic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes pore characteristics are associated with other textural features. For example, images of study by Török and Szemerey-Kiss [79], showed that a coarser limestone which was less porous and presented a higher percentage of fine pores presented higher erosion than a finer limestone that was more porous and had a higher percentage of the higher radii pores (in freeze-thaw tests with stone and mortars, where, hence the possibility of some salt contribution could be pondered). Bioturbation in limestones has been reported to be susceptible to salt weathering erosion because of the association with iron oxides and porosity [71].…”
Section: Multiple Factorsmentioning
confidence: 99%